PERAN LEMBAGA ZAKAT DALAM MENINGKATKAN EFEKTIVITAS DAN AKUNTABILITAS PENGELOLAAN ZIS BAGI PEMBANGUNAN BERKELANJUTAN - Aisyah Frida Safira; Sania Mareta Fatta; Fauzia Fauzia Nur Zukhrufa (Journal Khafi : Journal Of Islamic Studies, 2025)
This research is aimed to study the strategic role of Zakat Institution in raising the effectiveness and accountability of Zakat, Infaq, and Charity management (ZIS). Using qualitative descriptive approach and literature study from various scientific sources, this study found that ZIS optimizing management needed management system base on the factual data, utilization of information technology, transparency and accountability in the report. The recommended strategies are strengthening basic data of Muzakki anc Mustahik, utilization zakat in the form productive program like micro business development, active involvement of the society through education and training program. The challenge involved the system information of zakat has not integrated yet, the quality and validity data which is very low, and lacked of society trust to the institution of zakat management.